Capacitive measurement system for liquid level measurement - Ruihua Xu; Bowen Wang; Min Zhang; Hossain, Nadim; Xu Zhang; Lili Yang (2016 5th International Conference on Computer Science and Network Technology (ICCSNT), 2016)
There are many types of liquid level measurement instrumentations in modern technology, including the multiple-liquid level measurement. However, there are some practical considerations that make them unfit to use in car washer tanks. They are often too expensive, too cumbersome, too awkward and unsuitable in tanks. Only a few of them are suitable enough for the technology to widely benefit their use in cars. As for advanced measurement technologies (e.g., hydrostatic, conductance, ultrasonic, radar and laser), they depend on essential digital computer intelligence. Furthermore, more advanced communication capabilities and digital calibration design can only be applied with the help of embedded microprocessor-based systems. In this report, a capacitive measurement system will first be designed. Then, a CDC circuit (capacitance-digital converter) will be established with proper control strategies. After that, a PIC microcontroller will act as the software interface to sample the data. The review of the documentation of technology, the overall design and the software interface will be provided together.